Repensando el extractivismo: La dependencia, el nacionalismo de recursos y la resistencia en América Latina - Ellner, Steve (Política. Revista de Ciencia Política, 2021)
This article centers on the dualities of the extractivist policies of twenty-first century Latin American governments. On the negative side, the extractivist megaprojects undertaken by multinational capital had a devastating environmental impact, in addition to the dispossession of Indigenous land. On the positive side, the resource nationalism promoted by “Pink Tide” progressive governments generated substantial revenue that was allocated to social programs. The article summarizes the thesis of writers of “neo-extractivism” (twenty-first century extractivism) and concludes that they exaggerate the homogeneity of the Pink Tide and conservative nations and pass over what most differentiates the governments with regard to extractivism: the conditions applied to foreign investment, such as taxes and labor rights, as well as the greater degree of state control of the economy.